Healthcare branding: Insights from Africa into health service customers’ repeat patronage intentions - Odoom, P.T.; Narteh, B.; Odoom, R. (International Journal of Healthcare Management, 2019)
The study explores the relationship between branding in healthcare, brand image and customer re-patronage intentions. A survey approach was employed to gather data from 318 outpatients in hospitals in the Accra Metropolis and the data was analysed using factor analysis and regression analysis. The results indicate that the four dimensions of healthcare branding – brand elements, tangibles, medical personnel quality and critical services – predict healthcare brand image and re-patronage intentions. However, brand elements did not predict customer re-patronage intentions; and a strong significant relationship emerged between healthcare brand image and re-patronage intention. The strategic implications of the results for managing branding in hospitals are discussed in the paper.
Research Article
Keywords: Healthcare branding; health marketing; hospital; brand image; repeat patronage intention; health service customer